Acts that kill and acts that do not : a philosophical analysis of the Dead Donor Rule - Tsai, Cheng-Chih (Array, 2021)
In response to recent debates on the need to abandon the Dead Donor Rule (DDR) to facilitate vital-organ transplantation, I claim that, through a detailed philosophical analysis of the Uniform Determination of Death Act (UDDA) and the DDR, some acts that seem to violate DDR in fact do not, thus DDR can be upheld. The paper consists of two parts. First, standard apparatuses of the philosophy of language, such as sense, referent, truth condition, and definite description are employed to show that there exists an internally consistent and coherent interpretation of UDDA which resolves the Reduction Problem and the Ambiguity Problem that allegedly threaten the UDDA framework, and as a corollary, the practice of Donation after the Circulatory Determination of Death (DCDD) does not violate DDR. Second, an interpretation of the DDR, termed "No Hastening Death Rule" (NHDR), is formulated so that, given that autonomy and non-maleficence principles are observed, the waiting time for organ procurement can be further shortened without DDR being violated.